Orca [videorecording (DVD)] - Vincenzoni, Luciano; Donati, Sergio; Harris, Richard, 1930-2002; Rampling, Charlotte, 1946-; Derek, Bo; Wynn, Keenan, 1916-1986 (Paramount, 2021)
When the giant whale's pregnant mate is maimed and killed by a fisherman, the whale seeks vengeance: smashing boats, attacking a seacoast village, and eventually luring his human adversaries to a final confrontation on the marine creature's own arctic turf.